Influence of reconstruction parameters for FBP in semiquantification of brain studies with 123I-FPCIT - Alves, Fábio (2015)
Brain dopamine transporters imaging by Single Photon Emission Tomography (SPECT) with 123I-FP-CIT has become an important tool in the diagnosis and evaluation of parkinsonian syndromes, since this radiopharmaceutical exhibits high affinity for membrane transporters responsible for cellular reabsorption of dopamine on the striatum. However, Ordered Subset Expectation Maximization (OSEM) is the method recommended in the literature for imaging reconstruction. Filtered Back Projection (FBP) is still used due to its fast processing, even if it presents some disadvantages. The aim of this work is to investigate the influence of reconstruction parameters for FBP in semiquantification of Brain Studies with 123I-FPCIT compared with those obtained with OSEM recommended reconstruction.